The Role of the Intestinal Microbiota in Nonalcoholic Steatohepatitis - Xiang, Hui; Sun, Dating; Liu, Xin; She, Zhi-Gang; Chen, Yonghong (Frontiers in Endocrinology, 2022)
Nonalcoholic steatohepatitis (NASH) is a serious disease threatening public health, and its pathogenesis remains largely unclear. Recent scientific research has shown that intestinal microbiota and its metabolites have an important impact on the development of NASH. A balanced intestinal microbiota contributes to the maintenance of liver homeostasis, but when the intestinal microbiota is disequilibrated, it serves as a source of pathogens and molecules that lead to NASH. In this review, we mainly emphasize the key mechanisms by which the intestinal microbiota and its metabolites affect NASH. In addition, recent clinical trials and animal studies on the treatment of NASH by regulating the intestinal microbiota through prebiotics, probiotics, synbiotics and FMT have also been briefly elaborated. With the increasing understanding of interactions between the intestinal microbiota and liver, accurate and personalized detection and treatment methods for NASH are expected to be established.